High-resolution magic angle spinning nuclear magnetic resonance (HR-MAS-NMR) as quick and direct insight of almonds. Issue 1 (2nd January 2020) - Salvo, Andrea; Rotondo, Archimede; Mangano, Valentina; Grimaldi, Manuela; Stillitano, Ilaria; D'Ursi, Anna Maria; Dugo, Giacomo; Rastrelli, Luca
Abstract: Almonds are the tasty seeds of Prunus dulcis plants globally appreciated for the pleasant palatability and remarkable nutritional value, therefore it is very spread as snack and as basic ingredient of the confectionery products. The HR-MAS-NMR is a simple spectroscopy able to directly and quickly explore the chemical composition of powdered seed samples dispersed in D2 O. 1 H spectra witness the remarkable presence of triglyceride fatty esters together with sucrose; other minor water soluble metabolites are also detectable. This very rough approach is effectively providing chemical profiles featuring almond samples. In this analysis we were able to statistically distinguish the "Avola" almonds from other marketed products submitted to the same analysis. This is just a first investigation based on the main compounds but it might pave the way toward the quantitative evaluation of many other compounds in the almond therefore implementing the HR-MAS-NMR knowledge of these precious seeds. Graphical Abstract: